Collaborative Governance Process in Supporting Public Private Partnership in Singkawang Airport Development in 2023-2024 - Maya Novita Sari; Nandang Alamsah Deliarnoor; Novie Indrawati Sagita (Dinasti International Journal of Education Management And Social Science, 2025)
This research is driven by the inadequacies in the collaborative process within the Public-Private Partnership (PPP) scheme, which has hindered the operationalization of Singkawang Airport, despite its inauguration by the President of Indonesia on March 20, 2024. The collaboration involves key actors, including the Central Government through the Ministry of Transportation, the Singkawang City Government, PT Penjaminan Infrastruktur Indonesia, CSR Team and the local community surrounding the airport construction site. Adopting the cross-sector collaboration framework proposed by Bryson, Crosby, and Stone, this study aims to analyze and elucidate the Collaborative Governance process in the development of Singkawang Airport by examining six dimensions: forging initial agreements, building leadership, building legitimacy, building trust, managing conflict, and planning. This study employs a qualitative research method, with data collected through interviews, observations, and document analysis. Informants were selected using purposive and snowball sampling techniques. The findings reveal that the Collaborative Governance process in the PPP scheme for Singkawang Airport is partially evident across the six dimensions. The first dimension, forging initial agreements, highlights the absence of formal agreements underpinning the collaboration. The second dimension, building leadership, demonstrates the presence of both formal and informal leadership structures. In the third dimension, building legitimacy, both internal and external legitimacy have been established. The fourth dimension, building trust, reveals that trust-building efforts are limited to periodic meetings conducted several months apart. The fifth dimension, managing conflict, shows a lack of preventive measures necessary to sustain trust. Finally, the sixth dimension, planning, indicates that while initial plans were formulated, they required dynamic adjustments to address emergent challenges during implementation. In conclusion, this study underscores that relying solely on the PPP scheme poses significant challenges to the realization of the airport project. Cross-sector collaboration has accelerated the development process but remains suboptimal, as it does not fully address the six dimensions of effective collaboration.